2011
DOI: 10.1080/15299716.2011.620802
|View full text |Cite
|
Sign up to set email alerts
|

An Update and Reflections on Fear of and Discrimination Against Bisexuals, Homosexuals, and Individuals with AIDS

Abstract: This study explored the relationship between biphobia, homophobia, AIDS phobia, an individual's sexual opinions and the orientation of an individual's past sexual behaviors and fantasies. Participants ( N = 224) completed five self-report measures designed to specifically assess these psychological constructs. There were statistically significant correlations between the participants' fear and discrimination of sexual minorities and individuals with AIDS. Additionally, the results suggest that more conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Third, because the sub-representation of HIV patients in this study, it is recommended that future HTO studies should include more such participants, preferably both patients who are and are not treated by the HAART, as HIV patients under HAART are expected to have better knowledge and opinions, which may effect their HTO level. It is also suggested that the effects of HTO on coping of HIV patients with its medical and psychosocial implications should be studied [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Third, because the sub-representation of HIV patients in this study, it is recommended that future HTO studies should include more such participants, preferably both patients who are and are not treated by the HAART, as HIV patients under HAART are expected to have better knowledge and opinions, which may effect their HTO level. It is also suggested that the effects of HTO on coping of HIV patients with its medical and psychosocial implications should be studied [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Personally, I find it ridiculous that being hate-crimed is construed as part of gay culture, as if it is something that LGBTQ+ people choose to do or sign up to be victims of, and not something invented and perpetrated by the dominant heterosexual culture. Additionally, I cannot help but wonder if the inclusion of 'knowing HIV-positive people' in a measure of cultural affiliation may irresponsibly contribute to the idea of HIV/AIDS as a gay disease (Wright et al, 2011). Due to such thinking, in New Zealand men still cannot donate blood for three months after having sex with another man, regardless of the parties' HIV status (Saxton, 2020).…”
Section: Critiques Of the Literaturementioning
confidence: 99%